Attachment and Concord of Temporal Adverbs: Evidence From Eye Movements - Biondo, Nicoletta; Vespignani, Francesco; Dillon, Brian (Frontiers in Psychology, 2019)
The present study examined the processing of temporal adverbial phrases such as “last week,” which must agree in temporal features with the verb they modify. We investigated readers’ sensitivity to this feature match or mismatch in two eye-tracking studies. The main aim of this study was to expand the range of concord phenomena which have been investigated in real-time processing in order to understand how linguistic dependencies are formed during sentence comprehension (Felser et al., 2017). Under a cue-based perspective, linguistic dependency formation relies on an associative cue-based retrieval mechanism (Lewis et al., 2006; McElree, 2006), but how such a mechanism is deployed over diverse linguistic dependencies remains a matter of debate. Are all linguistic features candidate cues that guide retrieval? Are all cues given similar weight? Are different cues differently weighted based on the dependency being processed? To address these questions, we implemented a mismatch paradigm (Sturt, 2003) adapted for temporal concord dependencies. This paradigm tested whether readers were sensitive to a temporal agreement between a temporal adverb like last week and a linearly distant, but structurally accessible verb, as well as a linearly proximate but structurally inaccessible verb. We found clear evidence that readers were sensitive to feature match between the adverb and the linearly distant, structurally accessible verb. We found no clear evidence on whether feature match with the inaccessible verb impacted the processing of a temporal adverb. Our results suggest syntactic positional information plays an important role during the processing of the temporal concord relation.